(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This thesis explores the use of flashcards and other supportive tools in language learning. It investigates how these tools can enhance vocabulary acquisition, reinforce language concepts, and support overall language proficiency. The research examines various methods of employing flashcards and similar resources, their effectiveness, and their integration into diverse learning environments.